Romowie a edukacja w kontekście pedagogicznym i andragogicznym - Balvín, Jaroslav; Novotná, Jarmila (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The upbringing and education students from other the majority groups of the population puts higher demands on teachers. This is accountable to the specifics of the cultural and social background of these students, particularly students of Romani descent. Given the situation with 300,000 Roma living in the Czech Republic, and about half a million in the Slovak Republic, nearly every teacher may meet Romani students at the schools. Preparation of teachers for the specifics of the Romani culture is therefore important, as it helps teachers in the pedagogic sphere form relationships with Romani children and adolescents, as well as in the andragogical sphere with Romani parents.